Keanekaragaman Vegetasi Rawa di Kecamatan Tanjung Lago - Siti Indah Oktaviani; Didi Jaya Santri; Endang Dayat (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2015)
The study aims to determine the diversity of vegetation swamp ecosystems in the district of Tanjung Lago. The study was conducted from June to July 2011. Methods of analysis using squares method, quantitative data analysis conducted on the value of density, dominance, frequency, importance and diversity index of each type of plant. The results showed that the vegetation consists of 16 genuses and 21 species dominated by Pteridophyta and Spermatophyta. vegetation diversity value of (2.0680), the higher the number, the higher the index type of diversity of a kind. Such characteristics are caused by environmental influences owned as organic matter content and low pH and factors derived human intervention.